Sodium 4-Carboxymethoxyimino-(4-HPR) a Novel Water-Soluble Derivative of 4-Oxo-4-HPR Endowed with In Vivo Anticancer Activity on Solid Tumors - Tiberio, Paola; Cavadini, Elena; Cleris, Loredana; Dallavalle, Sabrina; Musso, Loana; Daidone, Maria G.; Appierto, Valentina (Frontiers in Pharmacology, 2017)
4-oxo-4-HPR, an active polar metabolite of the synthetic retinoid 4-HPR, was shown to exert promising antitumor activity through at least two independent mechanisms of action. Specifically, differently from 4-HPR and other retinoids, 4-oxo-4-HPR targets microtubules and inhibits tubulin polymerization causing mitotic arrest and on the other hand, analogously to the parent drug, it induces apoptosis through the activation of a signaling cascade involving the generation of reactive oxygen species. However, the potential in vivo use of 4-oxo-4-HPR is impaired by its poor solubility. By chemical modification of 4-oxo-4-HPR, a new class of compounds with improved solubility and in vivo bioavailability was obtained. We demonstrated here that, among them, the most promising molecule, sodium 4-carboxymethoxyimino-(4-HPR), was endowed with in vitro antitumor efficacy and entirely preserved the double mechanism of action of the parent drug in cancer cells of different histotypes. In fact, the retinoid induced the activation of the apoptotic cascade related to the generation of reactive oxygen species through endoplasmic reticulum stress response and upregulation of phospho c-Jun N-terminal kinases and PLAcental Bone morphogenetic protein, leading to cell death through caspase-3 cleavage. Otherwise, sodium 4-carboxymethoxyimino-(4-HPR) caused a marked mitotic arrest coupled with multipolar spindle formation and tubulin depolymerization. To assess the compound antitumor activity, in vivo experiments were performed in three mouse xenograft models (ovarian and breast cancers and mesothelioma). The in vivo results demonstrated that retinoid administration as single agent significantly increased the survival in ovarian cancer xenografts, induced a statistically significant decrease in tumor growth in breast cancer xenografts, and caused a 30% reduction in tumor growth in a mesothelioma mouse model. Even though further studies investigating 4-carboxymethoxyimino-(4-HPR) toxicity and in vitro and in vivo activities in combination with other drugs are required, the double mechanism of action of the retinoid coupled with its in vivo antitumor efficacy and potential low toxicity suggest a promising therapeutic potential for the compound in different solid tumors.